Mortality of middle aged white South African gold miners. - Wyndham, C H (1986)
A cohort of 3971 white miners in South Africa, born between 1 January 1916 and 31 December 1930 who were alive on 1 January 1970 and currently working in the East Rand-Central Rand-West Rand mining areas, was followed up for nine years, when the 3426 survivors were aged from 48 to 62. Fifteen (0.4%) had been lost to view and 530 had died (13.4% of the 3956 whose vital status was determined). Based on the occupational histories of a 30% sample of the cohort it was known that the vast majority were gold miners. An estimated 93% had worked more than 85% of their mining service in gold mines. Standardised mortality ratios were calculated as the ratios of the deaths observed in the cohort to those expected on the basis of concurrent mortality in the reference population--the total white male population in the Republic of South Africa. There was little sign of a "healthy worker effect"; of several possible reasons, one is that the white miner in South Africa had adopted certain unhealthy life styles, another is that the reference population was otherwise inappropriate. The SMR for all causes of death (117.6) was raised because of excess mortality due to the following causes: lung cancer (161.2), chronic respiratory diseases (165.6), and acute and chronic nephritis (381.0). A case-referent analysis was carried out on those miners in the cohort who had spent at least 85% of their service in gold mines. For lung cancer, smoking was the main contributory factor towards disease. For chronic respiratory diseases bronchitis, emphysema, asthma, pneumoconiosis, and pulmonary heart disease), smoking was also the main risk factor, but there was an association wih cumulative dust exposure. Raised blood pressure, smoking, and adiposity were associated with ischaemic heart disease as was the duration of service underground. Study of comprehensive medical histories in all 530 deaths, including necropsy in most cases, showed that none was directly due to pneumoconiosis or to tuberculosis.